IEG Annual Report 2011 : Results and Performance of the World Bank Group - Independent Evaluation Group (Washington, DC: World Bank Group, 2015)
The work of the World Bank Group (WBG) in helping reduce poverty supports four core goals at both global and country levels: expanding economic opportunities, enhancing human development, mitigating socioeconomic and environmental risks, and improving governance and public sector effectiveness. In the first half of the 2000s, developing countries made advances in these areas, leading to a significant reduction in poverty. Historically high economic growth rates as well as improvements in key aspects of human development made the difference. A series of global economic crises as well as natural disasters contributed to setbacks, while global climate change continued to threaten progress. These global shifters need to be confronted by development strategies. Improving governance and public sector effectiveness is key to reducing poverty further. The quality of public sector management also affects the WBGapos;s development effectiveness in countries. WBG-supported country program and project outcomes are lower in countries with poorer quality public sector management, suggesting a need to augment the approach and prioritize engagement in this area. Finally, WBG managementapos;s adoption of recommendations derived from evaluations has increased over time, and both management and Independent Evaluation Group (IEG) have agreed on measures to improve this process.